Jensen Functionals on Time Scales for Several Variables. (10th April 2014) - Anwar, Matloob; Bibi, Rabia; Bohner, Martin; Pečarić, Josip
Abstract : We define Jensen functionals and concerned generalized means for several variables on time scales. We derive properties of Jensen functionals and apply them to generalized means. In this setting, we obtain generalizations, refinements, and conversions of many remarkable inequalities.